Delving Into Writing Anxiety of Rural College EFL Learners: A Quantitative Study - Mudra, Heri (OKARA: Jurnal Bahasa dan Sastra, 2023)
Anxiety in foreign language writing burdens EFL learners before, during, and after producing scientific written texts. This current research aimed to explore the types, levels, and causes of anxiety toward writing research reports and the final thesis of rural college EFL learners and the emerging causes of their writing apprehension. 103 EFL learners in two rural colleges in Indonesia participated in the quantitative study by employing the Second Language Writing Inventory (SLWAI) and the Causes of Writing Anxiety Inventory (CWAI). The results reveal that cognitive anxiety was the highest type and level of rural college EFL learners' writing apprehension. Independent t-test shows that female EFL learners dominate male learners regarding writing anxiety. Furthermore, junior learners were more anxious than seniors. The learners with writing training had lower anxiety than those without writing experiences. Moreover, the learners taking the Research Method course were anxious about writing a research report. However, no significant difference was found between each variable. The most dominant emerging factors deal with problems with linguistic matters, fear of lecturers or supervisors' negative feedback, self-regulation in writing, writing evaluation, and inadequate training in writing. In conclusion, current classroom practice in rural colleges needs to be aware of and take academic action towards such circumstances.